Drawbacks of hiring of foreign nurses - Ho, Sweet Lee *; Sri Ameera, Abdul Rahim *; Nitiakaliyani, Balasubramaniam * (Star Media Group Berhad, 2023)
Like many other countries, Malaysia is grappling with a significant shortage of nurses. Currently, there's a need for about 3,000 additional nurses in the nation's private hospitals.